The Issue of Training the Kazakh Traditional Singers. (Eurasian Journal of Philology Science and Education, 2015)
The article deals with problems which arise in connection with the dissemination (transmission)of the Kazakh musical heritage and the education of traditional music performers in contemporary environment.An important prerequisite for preserving vocal tradition is laying the theoretical foundations for Kazakh vocal performance, in particular, for the voice training of traditional singers. The review of the available(quite limited) sources, which is presented in the article, shows that the issue remains poorly understood, and musical education institutions teach the subject of voice training on primarily empirical basis. The author raises the issues of vocal tradition in connection with the primary goal of his scientific research, which is the development of the curriculum and methodology for primary school education for the Kazakh traditional music performers, viz. those who perform in vocal and instrumental genre of әn (i.e. singing with dombra). In addition, the article outlines key parameters for developing specific guidelines for education and vocal training of gifted children who specialize in traditional (folk) singing at primary musical education institutions (such as schools and colleges).
Keywords: Kazakh music; traditional singing; vocal training; teaching methodology